2023
DOI: 10.3389/fneur.2023.1086720
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-processed foods consumption is associated with multiple sclerosis severity

Abstract: BackgroundMS is a chronic inflammatory neurological and immune-mediated disease of multifactorial etiology. Ultra-processed foods (UPFs) have been generally considered unhealthy due to their poor nutritional value. Emerging evidence suggests that factors other than their nutritional content may play an additional role toward chronic inflammation.AimTo investigate the potential association of UPF consumption and MS severity in a group of MS Italian consecutive patients.MethodsDemographic (age, sex, marital stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…Likewise, the Mediterranean diet and other healthy dietary patterns also associated with reduced odds of FDE in case-control studies [121,122] . In contrast, pro-inflammatory diets (based on the dietary inflammation index [123] ) enriched in added sugars and ultra-processed foods are associated with increased FDE odds [124] and increased risk of autoimmune demyelinating diseases [125,126] . Corroborating these findings, a case-control study reported that low intake of fiber, vitamin D, and α-linolenic acid associated with increased odds of FDE [127] .…”
Section: Dietary Impacts On Fdesmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, the Mediterranean diet and other healthy dietary patterns also associated with reduced odds of FDE in case-control studies [121,122] . In contrast, pro-inflammatory diets (based on the dietary inflammation index [123] ) enriched in added sugars and ultra-processed foods are associated with increased FDE odds [124] and increased risk of autoimmune demyelinating diseases [125,126] . Corroborating these findings, a case-control study reported that low intake of fiber, vitamin D, and α-linolenic acid associated with increased odds of FDE [127] .…”
Section: Dietary Impacts On Fdesmentioning
confidence: 99%
“…In the absence of clinically-validated nutritional recommendations to advance specific diets that are effective and safe for mitigating MS-ADON, the following section provides dietary guidelines that we posit may prove efficacious based on the multiple mechanisms putatively involved with this ocular sequel: (1) Diets stressing whole foods while reducing or eliminating ultra-processed foods laden with added sugars, additives, hydrogenated fats, and sodium. This recommendation stems from the findings that ultra-processed food consumption associates with increased likelihood of an FDE [124,181] and with increased MS severity [125] . Furthermore, an abundance of dietary glucose promotes T H 17 cell differentiation [182] and auto-reactive T H 17 cells are implicated as primary drivers of ADON (eg [44,46] ).…”
Section: Potential Intersections Of Dietary Interventions and Ms-adonmentioning
confidence: 99%
“…Understanding whether dysbiosis is a cause or an effect of the disease and understanding its role in disease development is the goal of ongoing and future research. A diet low in fiber and rich in ultraprocessed foods may induce dysbiosis and predispose to the development of MS [27] and worsen stroke outcomes [26], while simultaneously a good dietary therapeutic strategy ameliorates the diseases via efficient changes in the microbiota. A better knowledge of these aspects will allow us to understand how diet could be used to intervene in certain pathological conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Emerging evidence suggests that adherence to the MedDiet might be associated with MS onset and progression [ 11 , 14 , 15 , 16 ], but studies are still scarce. In our previous publication [ 17 ] we reported that higher ultra-processed foods (UPFs) consumption was associated with moderate-to-high MS severity compared to lower consumption. Up to date, there are no data about the prevalence of MS in individuals with high consumption of UPFs but it is known that adhering to hyper-caloric diets high in animal-origin fats and sugars, like Western diets, can impact on the disease pathogenesis and course [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%